Investigating the Nexus among Poverty Alleviation, Unemployment, and Economic Development in Nigeria - Gbadebo, Salam Najeem; Ayofe, Alase Gbenga; Olatunji, Lamidi Sikiru; Joseph, Tonuchi Emmanuel (The Economics and Finance Letters, 2021)
The purpose of this study is to investigate the existing relationship between poverty alleviation programmes, unemployment, and economic development in Nigeria. Specifically, the study employed the Autoregressive Distributed Lag (ARDL) cointegration technique and Vector Autoregression (VAR) model to estimate the existing relationship between the variables, using time series data from the Central Bank of Nigeria (CBN). The findings revealed that poverty alleviation programmes have a significant positive impact on economic development in Nigeria, while unemployment has a significant negative impact on economic development in Nigeria within the period under review. It was also revealed that poverty alleviation programmes granger causes economic development, but economic development does not granger cause poverty alleviation programmes as expected. However, unemployment and economic development granger cause each other as expected. The study, therefore, concludes that any policy aimed at addressing poverty and unemployment, if properly formulated and executed, will promote sustainable economic development in Nigeria.